è¿ç”¨æƒ…æ™¯æ•™å¦æ³•æé«˜ä¸¹å¤§ä¸æ–‡ç³»å¦ç”Ÿä½¿ç”¨â€œèƒ½â€ä¸Žâ€œä¼šâ€çš„èƒ½åŠ› - Afrimonika, Yoanna; ., Ina; ., Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
æ‘˜è¦ï¼šæœ¬æ–‡çš„ä¸»è¦ç›®çš„æ˜¯äº†è§£æƒ…æ™¯æ•™å¦æ³•å¯¹å¦ç”Ÿå¦ä¹ åŠ©åŠ¨è¯â€œèƒ½â€ä¸Žâ€œä¼šâ€çš„æ•ˆæžœï¼Œæ˜¯å¦æœ‰æ•ˆæé«˜å¦ç”Ÿä½¿ç”¨åŠ©åŠ¨è¯â€œèƒ½â€ä¸Žâ€œä¼šâ€çš„èƒ½åŠ›ã€‚ç ”ç©¶å¯¹è±¡æ˜¯ä¸¹å¤§ä¸æ–‡ç³»2014å¹´çº§Aççš„å¦ç”Ÿï¼Œä¸€å…±æœ‰20åå¦ç”Ÿï¼ˆç”·ç”Ÿ2åï¼›å¥³ç”Ÿ18åï¼‰ã€‚ç ”ç©¶æ–¹æ³•æ˜¯æµ‹è¯•æ³•å’Œå®žéªŒæ³•ã€‚æ ¹æ®æœ¬æ–‡çš„æ•™å¦å®žéªŒä»¥åŠå‰åŽæµ‹çš„ ç»Ÿè®¡ä¸Žåˆ†æžï¼Œç¬”è€…äº†è§£åˆ°é€šè¿‡äº†æƒ…æ™¯æ•™å¦æ³•åŽ,å¦ç”Ÿå¯¹åŠ©åŠ¨è¯â€œèƒ½â€ä¸Žâ€œä¼šâ€çš„æ£ç¡®çŽ‡æ˜Žæ˜¾æé«˜äº†ï¼Œå¦ç”Ÿå¯¹â€œèƒ½â€ä¸Žâ€œä¼šâ€çš„æŽŒæ¡èƒ½åŠ›å¤§éƒ¨åˆ†éƒ½å·²ç»è¾¾åˆ°80%ä»¥ä¸Šã€‚è¿™è¯æ˜Žäº†æƒ…æ™¯ æ•™å¦æ³•èƒ½æœ‰æ•ˆåœ°æé«˜å¦ç”Ÿä½¿ç”¨åŠ©åŠ¨è¯â€œèƒ½â€ä¸Žâ€œä¼šâ€çš„èƒ½åŠ›ï¼Œä»Žè€Œå–å¾—æ›´å¥½çš„æ•™å¦æ•ˆæžœã€‚ å…³é”®è¯ï¼šåŠ©åŠ¨è¯ï¼›èƒ½ï¼›ä¼šï¼›æƒ…æ™¯æ•™å¦æ³• Abstract :The purpose of this research is to know the effect of situational teaching method for the student to learn auxiliary verb â€œnengâ€ and â€œhuiâ€, to know that if it can increase the student ability in using auxiliary verb â€œnengâ€ and â€œhuiâ€. The object of this research is Chinese language learners 2014 class A Tanjungpura University, with total students were 20 students (2 male; 18 female). The research method is a method of test and practice. Based on the analysis of the teaching learning process in the classroom and the result in pre-test and post-test, The writer gets the result after used the situational method that students test scores increased until 80%. It shows that the using of situational teaching method improve the studentâ€™s ability in using Auxiliary Verb â€œnengâ€ and â€œhuiâ€ effectively. In conclusion, it gives a good effect in studentâ€™s learning. Key words: Auxiliary Verb; neng;hui;Situasional Teaching Method